XLike: Cross-lingual Knowledge Extraction - Tadić, Marko (2014)
The goal of the XLike project is to develop technology to monitor and aggregate knowledge that is currently spread across mainstream and social media, and to enable cross-lingual services for publishers, media monitoring and business intelligence. The aim is to combine scientific insights from several scientific areas to contribute in the area of cross-lingual text understanding. By combining modern computational linguistics, machine translation, machine learning, text mining and semantic technologies we plan to deal with the following two key open research problems: (1) to extract and integrate formal knowledge from multilingual texts with cross-lingual knowledge bases, and ; (2) to adapt linguistic techniques and crowdsourcing to deal with irregularities in informal language used primarily in social media. The developed technology will be language-agnostic, while within the project we specifically address English, German, Spanish, Chinese as major world languages and Catalan, Slovenian and Croatian as minority languages.
Projekt MZOS
ENG